STRATEGI BRANDING DALAM PEMASARAN DI RUMAH SAKIT - Hilda Badruddin; Jaslis Ilyas; Wachyu Sulistiadi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
In the era of globalization, the hospital view is not only to carry out its social mission to improve public health but also to be profit-oriented. Therefore, marketing has an important role in the hospital industry. A good marketing strategy will be able to create welfare for patients, but also for the hospital's financial performance. The branding strategy in hospital marketing is a popular strategy at this time and is one of the strategies that are closely related to creating brand equity of the hospital. This study aims to further examine how branding strategy is in hospital marketing and its assessment of consumer loyalty and engagement. This study is a literature review of articles obtained from the ScienceDirect, ProQuest, and Scopus databases. a total of 7 articles were screened from 723 articles and reviewed. It was found that the strategy can create brand equity for the hospital organization as well as for a good relationship with health and patient loyalty.